PEMBUATAN ASESMEN INTERAKTIF MENGGUNAKAN COURSELAB DENGAN PENDEKATAN SCIENTIFIC PADA MATERI GERAK MELINGKAR KELAS X SMA - Srisa Oktaweri; Festiyed Festiyed; Yenni Darvina (Universitas Negeri Padang, 2017)
This research utilizes technology in make assessment is an attempt that can be done for optimize assessment to progress of students in learning process and giving direct feedback to answers given students in the assessment made. Aim of this research is produce a valid interactive assessment product, practical and effective use Courselab with scientific approach to class X Senior High School on circular motion materials. Research type oriented to R&D (Research and Development). Research object is interactive assessment using Courselab with scientific approach on circular motion materials and the test subject is the students of class X Senior High School 7 Padang. The data collection instruments used in this research are: expert validation sheet, practicality test sheet according to physics teacher, testability sheet of learners' response, and pre-test and post-test sheet.The results of data analysis show that interactive assessment using Courselab with scientific approach to Class X Senior High School on circular motion materials are on very valid criteria with an average percentage of 94%. At the product trial stage, the percentage of practical average of 81% was obtained with very practical criteria and gain score of 0.499 indicating effective interactive assessment used to improve learners' knowledge